(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The effect of ultraviolet rays (power, time and distance) on the seed quality indicators (germination rate, stem and root length resulting from seed nutrition stimulation and agglutination) of the Lazurniy variety of rice was determined. When the power of ultraviolet rays and the length of light were 30+30 W, the irradiation time was continued for 11 seconds, and the distance of irradiation to the seeds was applied at a height of 30 cm, the germination rate of the seeds was 98%, and the stem length was 9 cm and the root length was 7.5 cm as a result of seed nutrition stimulation and agglutination with rays. , compared to those not exposed to ultraviolet rays, the germination rate of seeds was 10.4%, the length of the stem was 4.7 cm, the length of the root It is stated that it is 3.5 cm higher.